2000
DOI: 10.1177/109634800002400301
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Citizenship Behaviors: Their Relationship to Organizational Effectiveness

Abstract: Organ’s organizational citizenship behavior (OCB) model implies that aggregate citizenship behaviors improve organizational effectiveness. This study investigated relationships between OCBs and organizational effectiveness indicators in limited-menu restaurants. Citizenship behaviors were associated with lower food cost percentages, increased revenue to full-time equivalent, perceived company quality, operating efficiency, customer satisfaction, and fewer customer complaints. Developing a work environment that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
154
3
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(184 citation statements)
references
References 19 publications
10
154
3
8
Order By: Relevance
“…Therefore, successful organizations need employees who will do more than their usual job duties and provide performance beyond expectations. Multiple studies and meta-analyses have been conducted to examine the relationship between OCBs and organizational performance and/or success [43][44][45]. These researchers found a positive and significant relationship between overall OCB and performance at the organizational level.…”
Section: Organizational Citizenship Behavior and Organizational Perfomentioning
confidence: 99%
“…Therefore, successful organizations need employees who will do more than their usual job duties and provide performance beyond expectations. Multiple studies and meta-analyses have been conducted to examine the relationship between OCBs and organizational performance and/or success [43][44][45]. These researchers found a positive and significant relationship between overall OCB and performance at the organizational level.…”
Section: Organizational Citizenship Behavior and Organizational Perfomentioning
confidence: 99%
“…The purpose of this assessment was to ensure that, after the results have given better insight into the process and predictors that lead to work engagement, work engagement itself is actually related to desirable outcomes in the workplace. Though OCB refers to behaviors that reflect going above and beyond the call of duty regarding their job description, it has been associated with such individual and organizational outcomes as performance evaluations, managers' reward allocation decisions, employee withdrawal, as well as efficiency, productivity, profitability, and costs of the organization (Allen & Rush, 1998;Chen, 2005;Dunlop & Lee, 2004;Ehrhart & Naumann, 2004;Koys, 2001;MacKenzie et al, 1991;Podsakoff & MacKenzie, 1997;Walz & Niehoff, 2000). The results of the hierarchical regression determining the relationship between work engagement and OCB confirm previous research findings that support a strong, positive relationship between these two variables (Babcock-Roberson & Strickland, 2010;Christian et al, 2011).…”
Section: The Conceptual Modelmentioning
confidence: 99%
“…In the context of knowledge creation, sharing and integration, these knowledge-related activities are inherently hard to measure and incentivize, and thrive best with weak incentives and less-controlling environments (e.g., Osterloh & Frey, 2000). Research has found that pro-social behaviors stimulate sales performance (Podsakoff & MacKenzie, 1994), operating efficiency (Walz & Niehoff, 2000), product quality (Podsakoff, Ahearne, & MacKenzie, 1997), as well as coordination, innovation, organizational development, and cohesion (see Organ, Podsakoff, & MacKenzie, 2006). …”
Section: Pro-social Motivation: Meaningmentioning
confidence: 99%